Análise Evolutiva dos Laboratórios Online - Cordeiro, Raúl (2017)
Our intention with this work is to analyze the evolution of online lab systems, from theirorigins in 1898, with the radio-controlled missile made by Nikolas Tesla,to the present day. We also propose to analyze the evolution of the severalonline labs lines of development throughout their history, in an attempt to foresee their future development, taking into consideration the factors that condition each particular line and the actual state of development. We also intend toanalyzewhy some development lines are deadand why they did not survive, especially when considering the human factors associated with each online lab system.We intend to prove that we can apply the “Origin of Species” laws in Online labs.